Antidiabetic efficacy of polar extracts of the leaves of tetracera indica merr. (dilleniaceae) in alloxanized rats - Ahmed, Qamar Uddin; Mat So'ad, Siti Zaiton (2011)
Background review: Plants are considered less toxic than synthetic drugs. Recently, the search for appropriate anti-diabetic agents has been focused on plants used in traditional medicine partly because of leads provided by traditional medicine to natural products that may be better treatments than currently used drugs responsible for serious side effects among diabetics. In folk remedies, leaves of Tetracera indica Merr. (Dilleniaceae) are effectively used in the treatment of diabetes. However, there is no scientific claim about its efficacy in the management of diabetes.